Cold surge activity over the Gulf of Mexico in a warmer climate1 - Pérez, Edgar P.; Magaña, Víctor; Caetano, Ernesto; Kusunoki, S. (Frontiers in Earth Science, 2014)
Cold surges are a dominant feature of midlatitude tropical interaction. During the North Hemisphere (NH) winter, midlatitude waves propagating from the Rocky Mountains into the Gulf of Mexico result in cold surges, also known as Nortes or Tehuantepecers, associated with severe weather over the southern part of Mexico. The magnitude of their intense surface winds, precipitation and drops in surface temperature depends on the characteristics of the midlatitude wave propagating into the tropics. The high spatial resolution (20 × 20 km) version of the TL959L60-AGC Model of the Meteorological Research Institute of Japan is used to examine changes in cold surge activity under the A1B greenhouse gas emission scenario for the 2080–2099 period. The model realistically reproduces the spatial and temporal characteristics of cold surges for the 1980–1989 control period. The effect of changes in baroclinicity, static stability and mean flow over North America suggest that in a warmer climate, increased cold surge activity over the Gulf of Mexico would occur. However, these systems would have shorter wavelength (higher phase speeds) and shorter lifespans that could reduce the total amount of winter precipitation. The increased frequency of cold surges over the Gulf of Mexico would be a consequence of weaker baroclinicity and static stability in the lower troposphere over the cold surge genesis region, along with more dominant westerly winds, resulting from ENSO-like conditions in the atmospheric circulations over North America.